PELATIHAN MICROSOFT WORD DAN MANAJEMEN FILE BAGI LEMBAGA DESA KAJANG DI DESA KAJANG KECAMATAN SAWAHAN - Latjuba Sofyana STT; Inung Diah Kurniawati; Abdul Rozaq; Arri Mushafaturrahman (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The demands of the times bring changes in various aspects of life. Technology has an important role in this era, because the joints of life are better connected with the support of information technology. One of the things that are demanded to be mastered by the community is the basic use of computers and Microsoft Office. Operating a computer is part of the skill set, so the device needs to have skills in operating computers in Windows and Microsoft Office. Microsoft word is a one-on-one Office program known as word processing software. It is necessary to increase the skills and ability to use information and communication technology for village officials.